A FOREGROUND ANALYSIS OF CLOCKS, DEAR LOVE, AND PATIENCE POEMS WRITTEN BY LANG LEAV - Alifia Noor Yasmine; Ika Oktaria Cahyaningrum; Titis Ary Laksanti I Desak Ketut; Yunita Widiyantari (PT Akselerasi Karya Mandiri, 2024)
Literature and linguistics stand oppositely. They almost cannot be related, but nowadays Linguistics and Literature can stand in one field of study called Stylistics. From stylistics, literature can be interpreted in linguistic ways and otherwise. This research aims to know the influences of foreground features in the interpretation of modern poems written by Lang Leav (Clocks, Dear Love, and Patience) and analyze the properties of particular linguistic construction metaphors in the three poems. This research is descriptive qualitative research because it analyzed the foreground features, classified the metaphor structure, and described the interpretation of all foreground and metaphors found in the three poems. The source of data for this research is the poems entitled Clocks, Dear Love, and Patience. Meanwhile, the data is all clauses from the selected poems. This research applied total sampling as a technique of sampling data because the population of the sample is less than 100 data.The results found in this research are the foreground features affect the interpretation and could lead to a new perspective that cannot be reached by Literary Criticism and the mapped metaphor in the poems leads to a different perspective from where it first appeared.